2015
DOI: 10.1590/s1806-66902015000100009
|View full text |Cite
|
Sign up to set email alerts
|

Economic evaluation of prebiotics, probiotics and symbiotics in juvenile Nile tilapia

Abstract: -This study aimed to evaluate economically the inclusion of prebiotics, probiotics and symbiotics in diets of Nile tilapia (4.07 ± 0.30 g), at two stocking densities (0.6 and 1.2 kg m -3 ). A total of 288 fish were distributed over 32 tanks (40 L) in a completely randomised design, in a 2 x 4 factorial (stocking density x additives), with four replications, over six weeks. The following were evaluated: total feed consumption (FC), final biomass (FB), relative gain in biomass (RGB), apparent feed conversion (AF… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
15
0
4

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(20 citation statements)
references
References 26 publications
1
15
0
4
Order By: Relevance
“…Regardless of the chosen probiotic, there are production costs, Azevedo et al (2015) observed best zootechnical performance and economic efficiency for Nile tilapia fed diet supplemented with prebiotics, probiotics, and symbiotics in the feed for Nile tilapia. Probiotic use in half (50%) of feeds offered per day, can guarantee the same result as fish fed with probiotic in all (100%) feeds.…”
Section: Resultsmentioning
confidence: 99%
“…Regardless of the chosen probiotic, there are production costs, Azevedo et al (2015) observed best zootechnical performance and economic efficiency for Nile tilapia fed diet supplemented with prebiotics, probiotics, and symbiotics in the feed for Nile tilapia. Probiotic use in half (50%) of feeds offered per day, can guarantee the same result as fish fed with probiotic in all (100%) feeds.…”
Section: Resultsmentioning
confidence: 99%
“…In aquaculture, MOS, fructooligosaccharides (FOS) and galactooligosaccharides (GOS) are the prebiotics most often selected to be integrated with probiotics, including E. faecalis , Pediococcus acidilactici and Bacillus licheniformis , to form synbiotics (Azimirad, Meshkini, Ahmadifard, & Hoseinifar, ; Modanloo, Soltanian, Akhlaghi, & Hoseinifar, ; Rahimnejad et al, ; Zhang et al, ). Although the mechanisms of MOS utilization by Bacillus and Enterococcus probiotic bacteria remain unclear, several studies have illustrated the positive impact of MOS on the gut microbiota and have definitively shown their roles as growth promoters in aquaculture (Azevedo et al, ; Daniels, Merrifield, Ringø, & Davies, ). The principle of synbiotics is that the prebiotics in synbiotics are metabolized to their respective sugars in the fish alimentary tract and are subsequently utilized by probiotic bacteria as sources of carbon (Goh & Klaenhammer, ).…”
Section: Discussionmentioning
confidence: 99%
“…Alguns estudos têm demonstrado os efeitos benéficos dos prebióticos e dos probióticos para peixes, como melhora na utilização do alimento, modulação da microflora intestinal, aumento da resposta imune e antagonismo a patógenos, o que gera maior sobrevivência dos peixes (Verschuere et al, 2000;Ringo et al, 2010;Azevedo et al, 2015). Contudo, apesar do sucesso obtido pela suplementação isolada de prebióticos e probióticos, poucos estudos avaliaram sua suplementação conjunta na piscicultura, em especial na larvicultura de espécies ornamentais.…”
unclassified